In-Situ Coating of Iron with a Conducting Polymer, Polypyrrole, as a Promise for Corrosion Protection - Stejskal, Jaroslav; Jurča, Marek; Trchová, Miroslava; Prokeš, Jan; Křivka, Ivo (Materials (Basel, Switzerland), 2024)
Iron microparticles were coated with polypyrrole in situ during the chemical oxidation of pyrrole with ammonium peroxydisulfate in aqueous medium. A series of hybrid organic/inorganic core-shell materials were prepared with 30-76 wt% iron content. Polypyrrole coating was revealed by scanning electron microscopy, and its molecular structure and completeness were proved by FTIR and Raman spectroscopies. The composites of polypyrrole/carbonyl iron were obtained as powders and characterized with respect to their electrical properties. Their resistivity was monitored by the four-point van der Pauw method under 0.01-10 MPa pressure. In an apparent paradox, the resistivity of composites increased from the units Ω cm for neat polypyrrole to thousands Ω cm for the highest iron content despite the high conductivity of iron. This means that composite conductivity is controlled by the electrical properties of the polypyrrole matrix. The change of sample size during the compression was also recorded and provides a parameter reflecting the mechanical properties of composites. In addition to conductivity, the composites displayed magnetic properties afforded by the presence of iron. The study also illustrates the feasibility of the polypyrrole coating on macroscopic objects, demonstrated by an iron nail, and offers potential application in the corrosion protection of iron. The differences in the morphology of micro- and macroscopic polypyrrole objects are described.
Keywords: corrosion protection; carbonyl iron microparticles; conductivity; conducting polymer; resistivity; hybrid core–shell composites; iron; polypyrrole; magnetic properties